For better biomechanical understanding in the future - Luhtanen, P. (coachesinfo.com)
The purpose of this presentation has been to describe biomechanically actions in soccer mainly from point of view of skills. Emphasis has been addressed also for soccer boots, ground surfaces and shin guards. An important area of biomechanics including of soccer skills and environmental factors is muscle action especially during the technical performances. Muscle action and the regulation of neuromuscular functions is the basis of motor learning. The biomechanical principles and characteristics introduced in this paper are consequences of the mentioned total action and indirect proof for coaches from the internal mechanics of the player.